الهوية وسؤال النهضة عند فتحي المسكيني - معوش,هنية; نصرات,عمار (University of Eloued جامعة الوادي, 2024)
The article Amis to analyze the difficulties encountered in the task of revealing the true identity, including the actual existence liberated from all the idols of traditional identity, to be presented by the poor Arab thinker in the from of a new identity stemming from the sources of ourselves as freedom and choice that the self makes in complete separation from all that binds it to the ingredients the familiar as the ancients and moderns imagined it, whether western or Arab. Thus, the question "who are we" takes another problematic space in which the philosopher goes deeper than just belonging to the self and from it to humanity and freedom, and that is the task of real enlightenment that philosophy undertakes.
Keywords: الهوية; النهضة; التنوير; المسكيني; الكلمات المفتاحية: عربيّــة: الهوية،النهضة،الحرية،الإنسانية،التنوير،المسكيني فرنسيــة او إنجليزية: Identity; Renaissance; Freedom; Humanity; Enlightenment; The Poor..